2018
DOI: 10.18203/2320-1770.ijrcog20184148
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Doppler studies in prediction of perinatal outcome in intrauterine growth restriction

Abstract: Background: Fetal surveillance of the pregnancies that are complicated by IUGR is essential to improve fetal outcome. Colour Doppler studies of uteroplacental and fetoplacental circulation are useful in identification of hypoxemic status of the fetus and allows timely intervention in at risk fetuses. The present study was aimed to know the significance of colour Doppler studies in intrauterine growth restriction cases and to correlate with the perinatal outcome thus to offer better strategies for early diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 7 publications
3
7
0
Order By: Relevance
“…Kumbar et al [ 6 ] evaluated the role of Doppler parameters in IUGR babies and found that 50% of perinatal deaths were seen in cases showing absent diastolic flow and 100% in cases having reverse end diastolic flow. In Gaikwad et al, 50% mortality in cases of REDF and 33.33% mortality was seen in cases with AEDF [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Kumbar et al [ 6 ] evaluated the role of Doppler parameters in IUGR babies and found that 50% of perinatal deaths were seen in cases showing absent diastolic flow and 100% in cases having reverse end diastolic flow. In Gaikwad et al, 50% mortality in cases of REDF and 33.33% mortality was seen in cases with AEDF [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the study of Kavitha et al out of these 15, 14 cases had adverse perinatal outcomes [ 4 ]. Gaikwad et al found adverse perinatal outcomes in 63 (50.4%) patients [ 3 ]. Out of 59 (65.6%) adverse event outcome patients, most of the patients (20/74.1%) had PE without severe features followed by eclampsia (19/79.25%), PE with severe features (13/72.2%) and GDM (7/33/3%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations